Avoiding online game addiction among youngsters - ; Purnama, Muhammad Guntur Aji; Azizah, Oktavia Trian (Association for Scientific Computing Electrical and Engineering, 2018)
Teenagers give a change that is influenced from various activities conducted outside the family environment that is playing. The development of information technology has progressed very rapidly, as one form of technological development that is the internet. In line with the rapid development of Internet technology is also triggered the development of new game technology that uses the internet, known as online games, and the online game market share at most is the age of adolescence because of the difficult age in controlling themselves or still unstable in doing something. This is why teenagers are addicted to playing online games. There are factors that affect a person's online game addiction that is internal factors and external factors. Internal factors refer to the state of one's self, while external factors refer to around a person. The case of online game addiction gives a good positive and negative impact. The positive impacts include the addition of new friends, proficient in English, increased concentration and high imagination in making strategies, while the negative impact caused is the lack of socialization relationship to the environment, being indifferent, the concern for the surrounding becomes decreased, concentration decreased, and so forth. To handle someone not to be addicted to playing online games, it is necessary to take preventive measures such as fostering strong intentions to stop playing games, changing gaming activities with more useful activities, reducing time for playing games, reducing time hanging out with fellow gamers, and more etc.